Pengembangan Usaha Ekspor Kayu Manis UMKM di Kelurahan Simarito - Romario F D Purba; Rizky Sahertian; Dian G Purba; Yosi Saragih; Putri Khairunissa; Octa Saragih; Muhammad Fauzi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Indonesia is one of the world's main producers of cinnamon (Cinnamomum burmannii), but in the last five years, Indonesian cinnamon exports have decreased by around 10.13% per year. This decline is influenced by various factors that are closely related to competitiveness. As one of the plantation sub-sector commodities, cinnamon plays an important role in national economic development, especially in improving people's welfare. Cinnamon is used as an ingredient in food, beverages, medicines, cosmetics, and other industries. In addition to supporting income, this plant also contributes to environmental preservation, especially in river basins and conservation areas.Most of Indonesia's cinnamon exports come from areas such as Kerinci, West Sumatra, Central Java, and Yogyakarta, which are dominated by smallholder plantations. One of the MSMEs in Simarito Village, North Sumatra, is a cinnamon exporter with a capacity of 500-1000 tons per year. The success of this MSME is supported by the implementation of an effective STP (Segmentation, Targeting, Positioning) marketing strategy, product innovation, and a focus on quality and customer satisfaction. In an increasingly competitive market, developing marketing strategies and improving quality are the main keys to maintaining the sustainability of Indonesian cinnamon exports.